Penggunaan Sandiwara Boneka sebagai Strategi Kegiatan Belajar pada Pengembangan Bahasa di TK Rasyidul Jannah Sukarame Bandar Lampung - Suri, Dharlinda (Lentera: Jurnal Ilmiah Kependidikan, 2024)
on language development. Ability language is a skill by a child For disclose feeling through words And expression , so child can give information to others and can enrich treasury child . Ability language very important in stimulation since early, Because child age ready capable role active in communication. Strategy in developing capabilities speaking kindergarten students, one of only with use puppet play . The method used in this research descriptive with approach qualitative. This research that the use of the puppet show can develop speak ability on child Kindergarten age with puppet play media assistance. With this puppet media can stimulate motor skills, creativity, imagination, experimentation and exploration. By using this puppet play strategy it really attracts the attention of students, so that teachers and students are active and work together.